Novel solid cloisite tin catalyzed polymerization of L-lactide - Selukar, Balaji Sidram; Pandey, Asutosh Kumar; Nande, Smita Sunil; Bansode, Avinash Santram; Garnaik, Baijayantimala (Journal of Chemistry and Chemical Engineering, 2012)
A novel cloisite modified solid catalyst was prepared in a single step from commercially available starting materials for the first time. The ring opening polymerization of L-lactide and D-lactide using this cloisite modified solid catalyst resulted in homopolymers of 75,000 and PDI = 1.6 and the maximum molecular weight (Mw) i.e. 180,000 with PDI = 1.9 were obtained. The catalytic activity of cloisite modified solid catalyst was compared with the conventional stannous octoate catalyst and found superior to stannous octoate in all respect such as conversion, molecular weight and molecular weight distribution etc.. Moreover, the maximum molecular weight i.e. 180,000was obtained at 220 o C, whereas, transesterification reaction predominate in presence of stannous octoate. The linear structure was confirmed by quantitative 13C NMR Spectroscopy. Blend films were obtained by casting mixed solutions of poly (D-lactide) and poly (L lactide) at various compositions, and stereocomplex was formed at 50/50 composition with molecular weight of 75,000.